2018
DOI: 10.1177/1049909118812431
|View full text |Cite
|
Sign up to set email alerts
|

An Individual Housing-Based Socioeconomic Status Measure Predicts Advance Care Planning and Nursing Home Utilization

Abstract: Background: Socioeconomic status (SES) is an important determinant of disparities in health care and may play a role in end-of-life care and decision-making. The SES is difficult to retrospectively abstract from current electronic medical records and data sets. Objective: Using a validated SES measuring tool derived from home address, the HOUsing-based SocioEconomic Status index, termed HOUSES we wanted to determine whether SES is associated with differences in end-of-life care and decision-making. Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 46 publications
0
35
2
Order By: Relevance
“…50 The HOUSES index provides a unique opportunity to study the effect of individual-level SES on a variety of health care outcomes but has only been used once previously in the ICU setting. 44 This article is unique as it examines the interaction or effect modification between age and HOUSES index on critical illness outcomes. We used a cutoff age of 50 years and demonstrated that some outcomes showed significant differences associated with the interaction between age and SES status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 The HOUSES index provides a unique opportunity to study the effect of individual-level SES on a variety of health care outcomes but has only been used once previously in the ICU setting. 44 This article is unique as it examines the interaction or effect modification between age and HOUSES index on critical illness outcomes. We used a cutoff age of 50 years and demonstrated that some outcomes showed significant differences associated with the interaction between age and SES status.…”
Section: Discussionmentioning
confidence: 99%
“…34,[37][38][39][40][41][42][43] The HOUSES index has also been used once previously in an ICU cohort to examine rates of advance care planning, health care utilization, and discharge disposition. 44 To focus on the main outcomes (eg, association of HOUSES with ICU outcomes) and avoid distraction, we did not report association of other SES measures with ICU outcomes, and Juhn et al demonstrated moderate to good correlation of HOUSES with other SES measures (eg, education, income, Hollingshead index, and Nakao-Treas index), which was not surprising given that each SES measure may reflect different aspects of SES. More importantly, HOUSES tended to show stronger association with health outcomes (eg, overweight, low birth weight) and behavioral risk factor (eg, smoking exposure) in a dose-response manner, compared to other SES measures.…”
Section: Measurement Of Ses-houses Indexmentioning
confidence: 91%
“…Since its original validation, it has been widely used for clinical and epidemiological studies concerning a broad range of health outcomes and behaviors as well as health care delivery in children and adults. 6,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Identifying Areas of Observed and Expected Case Density for AEs…”
Section: Houses As An Individual-level Ses Measurementioning
confidence: 99%
“…The marginal results of the EU funding onto the convergence of economically lagging regions was also found by Pellegrini et al, [21], showing the estimated time of about 50-75 years under the current financial support mechanism. Gagliardi and Percoco [22] found spatial effects of EU cohesion policy, documenting the noticeable economic growth in rural regions around big urban agglomerations and no significant effects on purely rural regions, raising the questions about the effectiveness of direct payments under CAP umbrella in corresponding to the goals stated in CAP, especially increasing convergence and sustainability of rural regions, as the abovementioned growth should be associated with relocation of economic activities from urban agglomerations to its outskirts due to lower operating costs there and increasing individual housing trend [23]. The divergence, induced by EU funding, which biggest part is being allocated to CAP, between richer urban agglomerations economies and poorer rural regions was documented also by Wójcik [24].…”
Section: The Deficiencies Of Current Direct Payments Financial Mechanismmentioning
confidence: 99%